2023
DOI: 10.1063/5.0114892
|View full text |Cite
|
Sign up to set email alerts
|

In situ uniaxial pressure cell for x-ray and neutron scattering experiments

Abstract: We present an in situ uniaxial pressure device optimized for small angle x-ray and neutron scattering experiments at low-temperatures and high magnetic fields. A stepper motor generates force, which is transmitted to the sample via a rod with an integrated transducer that continuously monitors the force. The device has been designed to generate forces up to 200 N in both compressive and tensile configurations, and a feedback control allows operating the system in a continuous-pressure mode as the temperature i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…For the X-ray experiments, the uniaxial pressure was generated using a dedicated sample stick with a linear actuator generating the force. Integrated feedback mechanisms ensured a constant applied pressure during the temperature scans as described elsewhere ( 32 ). X-ray scattering experiments were carried out at the P21.1 beamline at PETRA-III.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For the X-ray experiments, the uniaxial pressure was generated using a dedicated sample stick with a linear actuator generating the force. Integrated feedback mechanisms ensured a constant applied pressure during the temperature scans as described elsewhere ( 32 ). X-ray scattering experiments were carried out at the P21.1 beamline at PETRA-III.…”
Section: Methodsmentioning
confidence: 99%
“…Hydrostatic pressure has long been considered as a way of tuning the stripe phase in cuprates, but it was found that the pressure effect on the 3D superconducting transition temperature in LBCO near 1/8 is quite modest, even with the loss of the long-range LTT structure ( 27 , 28 ). In-plane uniaxial stress has recently been shown to be a more efficient control parameter ( 29 – 37 ). It was shown that the 2D superconductivity in LBCO ( = 0.115) can be pushed toward 3D order by the application of strain ( 29 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation